Physical Activity, Screen Time, and Sleep Duration of Children Aged 6-9 Years in 25 Countries: An Analysis within the WHO European Childhood Obesity Surveillance Initiative (COSI) 2015-2017 - Whiting, Stephen; Buoncristiano, Marta; Gelius, Peter; Abu-Omar, Karim; Pattison, Mary; Hyska, Jolanda; Duleva, Vesselka; Musić Milanović, Sanja; Zamrazilová, Hana; Hejgaard, Tatjana; Rasmussen, Mette; Nurk, Eha; et al. (S. Karger AG, 2020)
Children are becoming less physically active as opportunities for safe active play, recreational activities, and active transport decrease. At the same time, sedentary screen-based activities both during school and leisure time are increasing.
Keywords: Physical inactivity; Surveillance; Sedentary behaviour; Active transport; Active play